The determinants and implications of corporate cash holdings in China - Xu, Yan (Curtin University, 2009)
Current research on corporate cash holdings is set within the contemporary corporate cash-holding conceptual framework established by Opler et al. (1999), which consist of the static trade-off theory, the pecking-order theory and the free cash-flow theory. Most empirical studies on this area are focused on developed markets. This study is the first investigation to comprehensively examine the determinants and implications of corporate cash reserves in a developing market namely China based upon a sample of publicly listed Chinese firms between 1998 and 2006.Current research on corporate cash holdings is set within the contemporary corporate cash-holding conceptual framework established by Opler et al. (1999), which consist of the static trade-off theory, the pecking-order theory and the free cash-flow theory. Most empirical studies on this area are focused on developed markets. This study is the first investigation to comprehensively examine the determinants and implications of corporate cash reserves in a developing market namely China based upon a sample of publicly listed Chinese firms between 1998 and 2006.By combining the abovementioned three non-mutually exclusive theories, this study proposes a new integrated trade-off theory. The integrated theory posits that there is a target level of cash reserves determined by weighing the demand for and supply of corporate cash reserves. The empirical results confirm the existence of target levels, and that firms adjust their actual levels of cash holdings toward the target levels rapidly. Among the three proxies for target cash reserves used, this study found that both the average industry cash reserves and the predicted cash value regressed from a series of firm characteristics were valid proxies. The latter proxy is believed to provide the most accurate estimation as it takes consideration of firm specific characteristics. Results indicate that the speed of adjustment of cash holdings in China is more rapid than the speed of adjustment found in developed countries and the speed of adjustment relating to capital structure changes.This study also investigates how maintaining persistently excess cash reserves (PECR) affects firms’ subsequent investment behaviours. The results indicate that firms maintaining PECR have significantly more investment expenditures, as well as less financial constraints as indicated by reduced investment-cash flow sensitivity in subsequent years. This finding enriches the literature pertaining to financial flexibility as the status of PECR can serve as a good proxy for financial flexibility. Additional analysis indicate that PECR status has diminishing effect on subsequent short term debt, long term debt, and equity financing, consistent with the financing hierarchy set by the pecking order theory. Further analysis provides empirical evidences that in those PECR firms, there is no evidence of investment financial constraints, but the problem of over investment is serious.